PERAN GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM MENCEGAH RADIKALISME DI SMK N 6 SURAKARTA TAHUN AJARAN 2023/2024 - Damayanti, Aqilah Nurullia; Firmansyah , Kholis (Borneo : Journal of Islamic Studies, 2024)
The problem in this study is the rampant radicalism among high school students or equivalent in Indonesia. One of the causes could be due to the lack of a valid understanding of Islam. Therefore, the purpose of this study is to determine the role of Islamic Religious Education teachers in preventing radicalism at SMK N 6 Surakarta. This study is qualitative descriptive field research. Data collection techniques used are observation, interviews, and documentation. Data validity checks are carried out by triangulation of sources and triangulation of methods. Data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the role of Islamic Religious Education teachers in preventing the emergence of radicalism is by teaching moderate understanding in schools, providing materials to prevent radicalism, teaching correct religious understanding through the learning process and extracurricular activities, and supervising religious spiritual activities.